2018
DOI: 10.1097/md.0000000000010344
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral macular choroidal neovascularization—a rare manifestation in acute myelocytic leukemia

Abstract: Rationale:Characteristic signs of leukemic retinopathy include bilateral intra-retinal hemorrhage, white-centred hemorrhage, macular hemorrhage and cotton-wool spots. Capillary closure, retinal microaneurysms and neovascularization following massive fundus hemorrhage could be involved in few of the above instances. However, single choroidal neovascularization (CNV) in macular has not been observed in acute myelocytic leukemia (AML).Patient concerns:A 22-year-old woman presented with a 7-day history of vision d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Our results are comparable to the qualified tube surgery success rate of 63% reported by Gedde et al from the 1-year outcome data of the tube vs trabeculectomy study. 2 There was no significant difference between the two groups in both early and late complications as shown in Table 2. Our complication rates are consistent with…”
Section: Comparison Between Surgical Outcomes Of Glaucoma Drainage Immentioning
confidence: 78%
See 2 more Smart Citations
“…Our results are comparable to the qualified tube surgery success rate of 63% reported by Gedde et al from the 1-year outcome data of the tube vs trabeculectomy study. 2 There was no significant difference between the two groups in both early and late complications as shown in Table 2. Our complication rates are consistent with…”
Section: Comparison Between Surgical Outcomes Of Glaucoma Drainage Immentioning
confidence: 78%
“…1,3 Patients usually present with bilateral anterior uveitis, with or without hypopyon, mimicking HLA-B27-associated uveitis. [1][2][3][4] They can also present with isolated posterior uveitis or panuveitis mimicking the appearance of endogenous endophthalmitis. 2 Two main hypotheses have been suggested for pathophysiology: an immune reaction to dead MAC cell wall proteins, which is supported by an experiment of producing uveitis in mice with Freund's adjuvant and bacterial cell wall proteins, or direct drug-toxicity reaction, which is supported by observing higher serum level when fluconazole or clarithromycin was administered concomitantly.…”
Section: Rifabutin-associated Acute Bilateral Panuveitis Mimicking Enmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only one case report of a secondary choroidal neovascular membrane (CNVM) reported in acute myeloid leukaemia (AML) . Yang et al described a 22‐year‐old woman with acute vision loss and CNVM confirmed by ocular coherence tomography‐angiography (OCTA) in the context of recent chemotherapy for AML . We report a patient with CNVM in acute lymphoblastic leukaemia (ALL), which was successfully treated with bevacizumab.…”
mentioning
confidence: 91%
“…Direct infiltration cases are uncommon, including foveal infiltrates, macular lesions and retinal infiltrate . There is only one case report of a secondary choroidal neovascular membrane (CNVM) reported in acute myeloid leukaemia (AML) . Yang et al described a 22‐year‐old woman with acute vision loss and CNVM confirmed by ocular coherence tomography‐angiography (OCTA) in the context of recent chemotherapy for AML .…”
mentioning
confidence: 99%